Research areas in adult and continuing education. Issue 1 (1st April 2014) - Zawacki-Richter, Olaf; Röbken, Heinke; Ehrenspeck-Kolasa, Yvonne; von Ossietzky, Carl
Abstract : This study builds upon a Delphi study carried out by Zawacki-Richter (2009) which posited a validated classification of research areas in the special area of distance education. We now replicate the study for the broader field of adult and continuing education (ACE). The aims of this paper are: firstly, to develop a categorisation of research areas in ACE; secondly, to identify the most important areas; and thirdly, to identify the most neglected research areas in ACE. Based on a literature review and a Delphi study, three broad levels with 28 research areas have been derived to organise the body of knowledge in ACE. Prospective researchers can use the results to identify gaps and priority areas, and explore potential research directions.